PHENOL COEFFICIENT OF DISINFECTANT PRODUCTS DISTRIBUTED IN A SUPERMARKET OF LUBUK PAKAM - Fahma - shufyani; Asti Pratiwi; Wantrio Pardomuan Siringoringo (Jurnal Penelitian Farmasi & Herbal, 2018)
Disinfectant products distributed in Lubuk Pakam vary in types from different manufacturers. The disinfectant ingredients are phenol and quartenary ammonium. The potency of disinfectant for killing microorganisms needs to be evaluated to assure the quality of the products. This study was carried out to determine the effectivity of disinfectant products based on phenol coefficient. Phenol coefficient testing of disinfectant products was microbiologically performed against Salmonella typhi. The disinfectant solutions were prepared by diluting the sample in sterile distilled water in ratio of 1:5, 1:10, 1:20, 1:30, 1:40, and 1:50. Phenol solution (5%, w/v) was used as disinfectant standard. The growth of bacteria was observed at the exposure time of 5, 10, and 15 minutes. The results indicated that the phenol coefficient of product A, B, C, D, E, F, and G were 2.38, 2.00, 3.00, 3.38, 2.38, 2.63, and 3.00, respectively. Statistical analysis using Kruskal-Wallis test showed that the quality of desinfectant products was significantly different (p < 0.05). This study revealed that product A, B, C, D, E, F and G distributed in many supermarket of Lubuk Pakam fulfilled the requirement of disinfectant activity. Product that contain HCl had the strongest activity than other disinfectant products.